Response Analysis of SMA Regency Bengkulu Selatan Students and Teachers' Needs for the Development of E-Module of Alter Current Electricity Materials - Oktavia, Titin; Risdianto, Eko; Putri, Desy Hanisa; Abdu, Muhammad; Endang, Endang (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2022)
The purpose of this study was to analyze the response to the need for e-module learning media in Bengkulu Selatan Regency for physics teachers and students of SMA N 1, SMA N 6 and SMA N 7. The research data were taken from a population of physics teachers and students from SMA N 1, SMA N 6 and SMA N 7 in South Bengkulu Regency. The data collection technique in this study was using a questionnaire filled out via google form. The data analysis technique in this study is a quantitative analysis technique and concluded qualitatively by using validity and reliability tests to determine valid and reliable questionnaires. The results of this study indicate that the instrument used is valid and reliable. This can be seen from the results of the validity test there is no data excluded (Excluded). Based on the results of the study, it was stated that students and teachers strongly agreed if an android-based e-module was developed on alternating current electrical material.